McGraw-Hill spelling - Cook, Gillian Elizabeth; McGraw-Hill School Division (New York : McGraw-Hill School Division, 1998)
Student texts accompanied by teacher's editions (TE), teacher's resource books (TRB), and supplemental resources.
Teacher's resource books (TRB) contain activity masters, assessment, home connections, and management tools.
TE = Teacher's Edition; TRB = Teacher's Resource Book.
Each vol. is a separate grade level : 1-6.
Keywords: Spellers; English language; Education, Elementary